ANALYSIS OF THE THEORY OF ISOLATION IN MODERN LINGUISTICS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article is devoted to the analysis of the existing linguistic literature. The problem of the isolation of the main and secondary members of the sentence is considered and a number of questions are singled out, from the study of which a general picture of this syntactic-stylistic phenomenon is formed, namely: the essence of syntactic-stylistic isolation.